Epistemological construction doctrine of the veterinary care defect phenomenon in forensic veterinary examination - I. Yatsenko (Law. Human. Environment)
To prove the guilt of a veterinary professional in causing harm to animal health, forensic veterinary examination plays an important role, as the expert’s opinion is a source of evidence in legal proceedings that helps law enforcement agencies or the court to correctly qualify the offence and establish the compliance of certain actions of a veterinary professional with the current legislation. However, the study of the problem of defects in veterinary care is not properly covered in Ukrainian scientific sources. The research aims to formulate a definition of the concept of “defects in veterinary care”, to identify the signs of this phenomenon in the aspect of forensic veterinary examination, to propose a classification of types of defects and to give their characteristics. The methodological basis of the study is a systematic approach due to the specifics of the topic of the work and involving the use of general scientific and special scientific methods, including analysis, synthesis, analogy; logical and semantic method; systemic and structural method; modelling method; comparative legal method. It is proved that a defect in the provision of veterinary care should be considered a situation where a veterinary professional performs poorly diagnostic, therapeutic, tactical, resuscitation, rehabilitation and other procedures, carries out preventive measures, and also performs professional duties improperly or fails to perform them, which causes or may cause negative consequences for the animal(s) in the form of a health disorder (disease, injury, mutilation, etc.) or cause death. The author’s definitions of the concepts of “non-performance or improper performance of professional duties by a veterinary practitioner”, “accident in veterinary practice”, and “professional error in veterinary practice” are proposed and their signs are outlined. It is shown that defects in veterinary care can be caused by both objective and subjective factors. A classification of defects in veterinary care is proposed: by stages of veterinary care, elements and nature of veterinary care, and legal basis. The practical significance of the study is that it forms the basis of the methodology for determining defects in veterinary care during forensic veterinary examination